SEBARAN DAN DINAMIKA PERTUMBUHAN BAMBU PETUNG (Dendrocalamus asper) DI KECAMATAN CANGKRINGAN KABUPATEN SLEMAN, YOGYAKARTA - , SAFII ROHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Petung Bamboo is one of important non-wood forest produce in the district of Cangkringan that is many utilized by community as building material/construction, craft, household furniture, ornament, foodstuff and many others. The type is potential to shore up society economic after Merapi eruption and also as conservation plants at the buffer zone. This research aims to know spread and dynamical of Petung bamboosâ growth at the district of Cangkringan. Method used is survey by purposive sampling. After doing pre-survey of 5 villages at the district of Cangkringan, each village is chosen 3 sub-villages that contain Petung bamboo. Each subvillage is chosen 10 lands ownership randomly. Measured data includes place highness, and dimension census of bamboo on the each sample. Data is tabulated and analyzed by descriptive qualitative. Research result shows that petung bamboo is spread evenly at the villages in the district of Cangkingan. Higher a place cause high growth and smaller diameter of bamboo. Dynamical of bamboosâ growth that consist of number of rebung, young bamboo, old bamboo and cluster wide is affected by place highness and felling intensity.